Environmental Resources Conservation through Sustainable Forest Management. (10th June 2016) - Coletta, Vittoria; Lombardi, Fabio; Altieri, Valeria; Bombino, Giuseppe; Marcianò, Claudio; Menguzzato, Giuliano; Marziliano, Pasquale A.
Abstract: Between XVIII and XX centuries, the forest resources in Calabria region (southern Italy) were intensively exploited and only political strengths, relatively recent, led to a re-establishment of forest cover. Thanks to these actions, from 1957 to 1980, reforestation and forest recovery activities interested 153.000 ha and forest cover increased by 32%, with a consequent reduction of the erosion processes in mountainous areas. In the present study we analysed three monospecific conifer stands, reforested 50 years ago, in the Aspromonte National Park, dominated by calabrian pine, Monterey pine and silver fir, respectively. The long-term effects of the reforestation and the management implications were evaluatedin relation to the enhancement of the environmental resources of a modern Metropolitan city. All the reforested stands were highly productive. However, the lack of management often induced tree diseases and downfall, then loss of timber quality. Reforestation activities accomplished importance goals: (1) soil conservation; (2) timber production and (3) consequent socio-economic and employment advantages. However, in order to fulfil the long-term effects of such benefits, and to to enhance such resources within a Metropolitan city, is fundamental that forest policies should pay more attention to the management (holistic and sustainable), restoration and ecological stability of reforested stands, together with a constant monitoring of these reforested stands. Finally, reforested stands across all the Metropolitan areas play an important role in hydrological protection, water storage, but also for timber production.